Survival Outcomes in Men with Unfavorable Intermediate-Risk and High-Risk Prostate Cancer Treated with Prostate-Only versus Whole Pelvic Radiation Therapy. Issue 6 (27th June 2022) - Andruska, Neal; Fischer-Valuck, Benjamin W.; Waters, Michael; Juarez Diaz, Elizabeth; Agabalogun, Temitope; Kim, Eric H.; Smith, Zachary L.; Brenneman, Randall J.; Gay, Hiram A.; Andriole, Gerald L.; Michalski, Jeff M.; Baumann, Brian C.
Abstract : Purpose: Men with unfavorable intermediate-risk (UIR-PCa) or high-risk prostate cancer (HR-PCa) are often treated with definitive external beam radiotherapy (EBRT) plus androgen deprivation therapy. Treatment is frequently intensified by electively treating the pelvic lymph nodes (LNs) with whole pelvis radiotherapy (WPRT), but practice patterns and the benefits of WPRT are not well defined. We hypothesized that men treated with WPRT would have improved overall survival (OS) relative to men treated with prostate-only radiotherapy. Materials and Methods: National Cancer Database records of men diagnosed between 2008–2015 with UIR-PCa or HR-PCa and treated with prostate EBRT±androgen deprivation therapy (72–86.4 Gy) with (15, 175) or without (13, 549) WPRT were reviewed. Risk of LN involvement was calculated using the Memorial Sloan Kettering Cancer Center nomogram. Measured confounders were balanced with inverse probability of treatment weighting and OS hazard ratios (HRs) were generated using multivariable Cox regression. Results: Of the men, 53% received WPRT. Every 1% increase in risk of LN involvement correlated with a 1% increase in risk of death (p <0.001). WPRT trended toward improved OS in all men with UIR-PCa and HR-PCa (HR: 0.95 [95% CI: 0.90–1.006], p=0.055). WPRT correlated with improved OS in men with Gleason 9 and 10 disease (HR: 0.87 [0.78–0.98], p=0.02) or risk of LN involvement ≥10% (HR: 0.93 [0.87–0.99], p=0.03). Conclusions: Men with higher LN risk scores and Gleason grade benefited from WPRT. These results complement the recent POP-RT randomized trial in mostly positron emission tomography/computerized tomography-staged patients, demonstrating that a more heterogeneous population of men staged without functional imaging benefits from WPRT.